K2 rotation periods for low-mass hyads and the implications for gyrochronology - Douglas, Stephanie; Agüeros, M. A.; Covey, K. R.; Cargile, P. A.; Barclay, T.; Cody, A.; Howell, S. B.; Kopytova, Taisiya G. (The astrophysical journal, 2016)
As the closest open cluster to the Sun, the Hyades is an important benchmark for many stellar properties, but its members are also scattered widely over the sky. Previous studies of stellar rotation in the Hyades relied on targeted observations of single stars or data from shallower all-sky variability surveys. The re-purposed Kepler mission, K2, is the first opportunity to measure rotation periods (P rot) for many Hyads simultaneously while also being sensitive to fully convective M dwarf members. We analyze K2 data for 65 Hyads and present P rot values for 48. Thirty-seven of these are new measurements, including the first P rot measurements for fully convective Hyads. For 9 of the 11 stars with P rot in the literature and this work, the measurements are consistent; we attribute the two discrepant cases to spot evolution. Nearly all stars with masses ≲0.3 M ⊙ are rapidly rotating, indicating a change in rotation properties at the boundary to full convection. When confirmed and candidate binaries are removed from the mass-period plane, only three rapid rotators with masses ≳0.3 M ⊙ remain. This is in contrast to previous results showing that the single-valued mass-period sequence for ≈600 Myr old stars ends at ≈0.65 M ⊙ when binaries are included. We also find that models of rotational evolution predict faster rotation than is actually observed at ≈600 Myr for stars ≲0.9 M ⊙. The dearth of single rapid rotators more massive than ≈0.3 M ⊙ indicates that magnetic braking is more efficient than previously thought, and that age-rotation studies must account for multiplicity.
Gesehen am 27.04.2020